Resisting Power: Analyzing Power Abuse and Resistance in Ridley Scott’s ’The Last Duel’ through Foucauldian Lens - Ali Idris (Morphosis: Journal of Literature, 2024)
This study is entitled “Power Abuse in The Last Duel Film”. This study aims at analyzing the power abuse committed by a count Pierre against a noble Jean and how Jean deals with the power abuse against him. The object of the study is taken from a film entitled The Last Duel (2021), directed by Ridley Scott. This study uses the qualitative method to present the findings in both essay and picture form by examining the narrative and cinematography elements. Moreover, Michel Foucault’s theory regarding power, power relations, and power resistance is used to address the issues presented in the film. Foucault’s theory dictates that the goal is to understand what it means to be human subjects, which implies that studying power relations and power abuse is part of a bigger picture where power relations are a mode of actions on possible actions exercised towards others and power resistance is a response against the power abuse. The results of the study show that the count abuses his power through coercion, authority, and persuasion that harms Jean in terms of wealth and dignity. At the same time, Jean displays power resistance against the power abuse by suing Pierre and proposes for a duel to the death against his confidant. Keywords: Power abuse, power relations, power resistance.